Surveys of Informal Sector Enterprises - Some Measurement Issues - Kaushal Joshi; Rana Hasan; Glenita Amoranto (Asian Development Bank (ADB), 2009)
The informal sector represents an important part of the economy and the labor market in many countries, especially developing countries. Measurements of the informal sector are of intrinsic interest in their own right and contribute toward exhaustive measures of gross domestic product (GDP). Considering that the informal sector provides employment for income creation to a large number of poor and contributes significantly to the GDP of many developing countries, collecting statistics through surveys for accurate measurement of output, net surplus, and value added is critical for national accountants, other users, and for researchers working on policy-related issues. As most of the informal sector enterprises do not maintain business accounts, the survey responses depend highly on the recall by the respondent and the skills of the interviewer. Thus, a very important aspect of the surveys of informal sector enterprises is the design of the survey questionnaire and the details to be captured in data collection in order to accurately measure the characteristics of these enterprises. The details sought in the survey questionnaire have implications on the accuracy of data and hence in the measurement of expenditure, receipts, profits, and gross value added (GVA) of these enterprises. In this paper we examine the differences in the measures of: (i) profits of an enterprise derived from a detailed set of questions on incomes and expenses, versus profits obtained through a single direct question; and (ii) GVA obtained using the production approach as the difference of output and intermediate consumption from a detailed set of questions on incomes and expenses, versus GVA using the income approach by asking a few questions on factor incomes, and a single direct question on profits. We use data from the 56th round survey of unorganized manufacturing conducted by the National Sample Survey Organization of India during the period July 2000–June 2001. We also examine if the differences vary with the characteristics of the enterprises, and suggest further empirical research to develop suitable tools for providing accurate measurements of informal sector enterprises.
hdl:11540/1843
Keywords: 330; informal sector; informal sector enterprises; measurement of GDP; survey questionnaires; enterprise profits